The tyrosine aminotransferase from Trypanosoma rangeli: sequence and genomic characterization - Bontempi, Esteban (2000)
Fil: Bontempi, Esteban. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.